6 The age of the carer has an impact on the burden of care experienced by the carer. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Mukhtar, F; Raja, U; Singh, S; Lovell, N; Yi, D; Higginson, IJ
Abstract : Context: Those caring for people with chronic illnesses report high levels of unmet needs. Carers for patients with chronic illnesses must learn how to adapt with the demand of looking after a patient with a deteriorating condition. This can lead to increased stress due to sacrifices such as less time for socialising/financial difficulty. Objectives: To evaluate whether the age of the carer has impact on the burden experienced from caring for patients. Understanding the effect of caring for patients with chronic breathlessness and its burden would help interpret the results drawn from the main analysis of the OPTBreathe study, which investigated the preference for the breathlessness support service. Methods: Answers to the carer burden inventory (CBI), included in the face to face interviews with carers were analysed by carer's age. Categories of age were generated and answers to CBI items were converted into a total burden score. and synthesised by the scoping review of literature on the carers' wellbeing. relationships within the data and relating it to the results of other studies related to the wellbeing of cares. This includes journals and qualitative studies. Results: 65 carers completed 20 items in the CBI, The average age was 65 and 9 of 65 carers were men. 49/65 stated being either comfortable or coping on their current income, whereas only 10/65 stated in financial difficulty. Average burden score was 18.9: 12.5 in age <40; 16.4 in 40–49; 18.3 in 50–59; 20.7 in 60–69; 20.3 in 70–79 and 17.4 in 80+. The graphical illustration showed that there was an increasing trend from the <40 age range. Conclusions: Though the relationship was not linear the results indicate that there is clear larger burden of care on older carers. Suggestions as to why include increased morbidities in older carers and increased financial burden.